A leap from negative to positive bond: A step towards project sustainability - Francesco Di Maddaloni; Roya Derakhshan (Administrative Sciences, 2019)
Departing from the normative formulation of stakeholder theory and building upon the current body of knowledge, this study aims to advance understandings on the benefits and challenges towards a more holistic approach to stakeholder management at the local level of major public infrastructure and construction projects (MPIC). Major construction projects, project managers, and the local community stakeholder are deemed to operate within a "negative bond". This interaction is elucidated through the attribution theory lens, which shape the conceptual framework of the study. This paper illustrates that a broader inclusiveness of stakeholder views into managerial decisions can initiate to break this negative bond and shift it towards positive relationships. An organization's conscious approach towards transparent communication with the local community stakeholder might help to shape a long-term perspective for better project benefits realization either at the national, regional, or local level. By "exceeding stakeholders needs and expectations", project managers and local communities can better collaborate in order to achieve sustainable development over time.
Keywords: 350; local community; attribution theory; communication; inclusiveness; sustainability